國小中高年級國語文教材事理類說明文學習內涵之探究 - 陳佳宜; 楊淑華; 黃慧文 (課程研究, 2008)
This study is based on the teaching materials of exposition in Mandarin textbook of three versions as the basis of study. First, generalize and treat the teaching materials and distribution of the reasoning exposition in Mandarin textbooks in grade 3-6 curriculum. Then accumulate the opinions of elementary school teachers by “checklist of the reasoning exposition” to inspect the materials, teacher’s manuals and workbooks. After that, analyze the content of the reasoning exposition of three versions and give advice to further editions. From the study, it is found that the subject arrangement of the exposition accords with the experience of the pupils approximately, the discrimination in the literary form is not explicit enough, the proportion of the exposition in the textbooks is low, the distribution and proportion of different type of expositions in three versions differs from each other very much, the composition of content is lack of the arrangement of ideas, the exercises of writing and expository feature